Advancing Towards Delay-Free Construction Project: A Review - Ansah, Richard Hannis; Sorooshian, Shahryar; Shariman, Mustafa; Duvvuru, Gomanth (IEOM Society, 2016)
This paper is in the form of discussion on the recent trend of construction projects delays, addressing the need for collaborative efforts among project parties and bolstering the use of robust techniques to handle the challenges confronting the industry. The paper begins with a review of delays in construction projects, trending methodologies and techniques, and highlights the potential for applying the strategies: Building Information Modeling (BIM); Computer Integrated Manufacturing (CIM); Production/Lean Techniques; Skill Development and Training; and Concurrent Supply Network (CSN). Extensive use of these approaches in many countries has proven its efficiency in construction project development process’ improvement and the overall performance of the building industry.